Habitable worlds with JWST : transit spectroscopy of the TRAPPIST-1 system? - Barstow, J; Irwin, P (Oxford University Press, 2016)
The recent discovery of three Earth-sized, potentially habitable planets around a nearby cool star, TRAPPIST-1, has provided three key targets for the upcoming James Webb Space Telescope (JWST). Depending on their atmospheric characteristics and precise orbit configurations, it is possible that any of the three planets may be in the liquid water habitable zone, meaning that they may be capable of supporting life. We find that present-day Earth levels of ozone, if present, would be detectable if JWST observes 60 transits for innermost planet 1b and 30 transits for 1c and 1d.